Studi Kasus Tindak Pidana Penganiayaan Terhadap Saksi Korban - Iskandar, Agung Samudra; Rahman, Muh. Sabir; Darwis, Muh. (Jurnal Litigasi Amsir, 2023)
This study aims to consider the legal considerations of judges in dropping cases of the abuse of witness victims in Parepare City (Case Study Number 117/Pid.B/2021/Pn.Pre), and the application of judges’ law in deciding the Abuse of witness victims in Parepare City (Study case Number 117/Pid.B/2021/Pn.Pre) The type of research used in this research is normative research. The legal material used is primary legal material, namely binding legal material consisting of basic norms or rules, namely the Criminal Code, Law number 8 of 1981 concerning criminal procedural law, Parepare District Court decision Number 117/Pid.B /2021/Pn.Pre. The results of the research The judge’s legal considerations in making a decision on the crime of persecution committed by the defendant in decision Number 117/Pid.B/2021.PN.Pre who received a sentence of imprisonment for 10 (ten) months was appropriate because, in the legal considerations by the judge, the defendant’s actions are actions that are legally and convincingly guilty been proven guilty of committing the crime of mistreatment of the witness victim SAPRI SIBE Alias SAPRI Bin LA SIBE, based on the facts at trial and there is no justification, the defendant is also a person who according to law is capable of being responsible answer, the application of criminal law by the judge against the defendant of the criminal act of abuse committed by the defendant against the victim-witness in decision Number 117/Pid.B/2021/PN.Pre Article 351 paragraph 1 of the Criminal Code; regarding persecution and the application of this article is appropriate because of the elements the elements of criminal acts in the article have been proven to have been fulfilled.